Desain Pencacah Serabut Kelapa dengan Penggerak Motor Listrik - Handoko Priono; Muhammad Yusri Ilyas; Aditya Riska Nugroho; Dimas Setyawan; Laili Maulidiyah; Rinasa Agistya Anugrah (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
Diesel Motor is a type of piston combustion motor commonly called Ignition Compression Engine Combustion Engine. The use of coconut fiber chopper machines using diesel drive engines in the market has not been able to increase consumer comfort and efficiency. Because of this issue that emits CO2 and NOx also causes air pollution and noise emissions, it tends to be relatively large and also requires intensive care that requires a lot of space and costs. This will renew the surrounding environment and allow user comfort and efficiency when running the machine. Therefore, it is necessary to have an efficient and optimal coconut fiber chopping machine by reducing noise so that it is not noisy and pollution-free. The coconut fiber enumerator with an electric motor drive is an enumerator of coconut fibers with an electric motor as a solution for making household products and agricultural fertilizers to increase comfort and efficiency for consumers so as to increase economic value in the community. This research method begins with making a tool consisting of a study of literature, measuring each component of the tool consisting of a frame, eye drive, motor drive, filter and pulley and designing the design model. Trial on a no-load blade shaft rotation of 450 rpm. At the time of enumeration, the shaft rotation is reduced to around 350-400 rpm and the linear velocity of the V-Belt is 3.9 m / s. From the coconut fiber chopper with an electric motor drive it causes low vibration, does not cause pollution nor is it efficient.